Evaluación de la percepción sobre seguridad turística en la ciudad de Guaranda, provincia bolívar, año 2023 - Sanchez Shilquigua, Karen Paola (2024)
The main objective of this research project is to evaluate the perception of tourist safety in the city of Guaranda, in order to have an information base to improve and strengthen the confidence of visitors in the destination. For the development of the study, a mixed methodology was used, i.e. a mixture of qualitative and quantitative approaches, qualitative by the bibliographic analysis carried out and quantitative by the data collection with numerical measurement. Similarly, research techniques and instruments were applied, such as surveys and interviews, through which results were obtained as follows; There are 11 key factors or indicators that influence the perception of tourist security in a destination, which are divided into public and private entities, and the identification of the security measures implemented by them and evaluated by means of a rating scale reflected in three aspects, good, bad and fair, according to the number of security measures they have, in order to know the effectiveness of these, Similarly, it was identified that the main concerns and needs of tourists are focused on the lack of signage within the city and the lack of infrastructure for the free movement of people with disabilities, while the concerns of local residents are focused on improving the condition of transportation units, such as the existing signage in the city of Guaranda. Key words: Tourist Safety, Perception, Indicators, Security Measures, Concerns, Tourists.